Adversarial risks in the lab – An experimental study of framing-effects in attacker-defender games. (December 2019) - Meng, Sascha; Wiens, Marcus; Schultmann, Frank
Highlights: Moral frameworks make average humans no good attackers in attacker-defender games. Framing causes defenders to make more rational decisions in attacker-defender games. Framing through wording and payoffs has similar effects. Abstract: We conducted an economic lab experiment to test for a two-player defender-attacker game the theoretical predictions and two variants of framing. We used framing to intensify the players' perceived conflict of interests in the underlying defender-attacker game by uniformly shifting payoffs (endogenous framing) and modifying wording (exogenous framing). Participants played both roles (defender and attacker). Our results show two main effects, which need to be considered in future lab experiments concerning decision problems with strong social conflicts. Firstly, ordinary human participants showed a too considerate behavior in the attacker role (attackers behaved too "soft"). Secondly, framing, which highlights the underlying conflict, causes participants in the role of the defender to act in a more rational way. The results of our study are relevant for the design of future experiments concerning high-conflict interactions.